The Effectiveness of Online Education Study Live Method on Reducing Hesitancy of the COVID-19 Vaccine - Eli Indawati; Abdul Khamid; Niki Herdian Permana (STIKep PPNI Jawa Barat, 2023)
Aim: The global vaccine refusal movement continues to exist. Indonesia has implemented a vaccination program to combat the COVID-19 pandemic in order to minimize transmission rates, fatality rates, break the chain, and acquire herd immunity. The Study Live Method is a hybrid method of offline merging as if online, when live zooming by employing additional Open Broadcaster software (OBS) to create running text. The purpose of the study was to evaluate the efficacy of online teaching via the Study Live Method in reducing COVID-19 vaccine hesitancy. Methods: The research method is a quasi-experimental design with a pre- and post-testing strategy and a control design. The population of Bekasi Municipality is 48 individuals. The sample approach utilized a method of purposive sampling and analysis was used an independent t test. Result: the average age of respondents in the intervention group is 41.71 with the youngest respondent age 18 years and the oldest 71 years old, while in the control group, the youngest respondent age 21 years old and the oldest 60 years old. The results demonstrated that in the intervention was significantly effective in reducing COVID-19 vaccine hesitatece group (p value 0.05). Conclusion: It is advised that the general population get digital health education in the context of introducing renewable technology and continuously integrated and integrated implementation in order to lessen the reluctance of the COVID-19 vaccination to boost herd immunity.